Analisis Sifat Mekanik Komposit Serat Sabut Kelapa dengan Perlakuan Alkalisasi Etanol dan Filler Arang Tempurung Kelapa - Taufan Putra Wahyu Hidayat; Ratna Dewi Anjani; Deri Teguh Santoso; Irvan (Jurnal Serambi Engineering, 2024)
Coconut trees are plants that are easily found in tropical areas such as Indonesia; therefore, natural products are abundant, but the use of waste from coconuts has not been processed into technological products. The aim of this study was to determine the differences in the variations in the volume fraction of fibers during tensile and impact strength testing. The variations in the volume fraction used were 5%, 10%, and 15% fiber, and the chemical treatment of the fiber was alkalized using 20% ethanol for 3h of soaking. Composite manufacturing uses a hand layup method with random fiber orientation. The results of the research on variations in volume fraction of 5%, 10% and 15% obtained test values, in tensile testing such as maximum load obtained 32,844 kgf, 106.44 kgf and 105.59 kgf, maximum stress 6.0510 N/mm2, 16,893 N/ mm2 and 17.249 N/mm2, elongation breaking strain 0.8150, 0.3275 and 0.2617, breaking strain 1.4818 %, 0.5955 % and 0.4758 %, for the tensile test value the impact energy value was found tobe 1.6 kgf, 2.3 kgf and 3.3 kgf and impact prices of 1.84 kJ/m2 , 2.45 kJ/m2 and 3.45 kJ/m2 . The high tensile and impact test results were due to mixing coconut fiber which had gone through ethanol alkalizing treatment with coconut charcoal powder to obtain high impact and tensile values